Magnetic anisotropy in spherical Fe16N2 core–shell nanoparticles determined by torque measurements - Eiji Kita; Kenichi Shibata; Yuji Sasaki; Mikio Kishimoto; Hideto Yanagihara (AIP Advances, 2017)
The magnetic anisotropy energy for core–shell α”-Fe16N2 nanoparticles was evaluated by the rotational hysteresis loss obtained from magnetic torque measurements. The saturation magnetization of the α”-Fe16N2 core was deduced from volume fractions of α”-Fe16N2 determined by an analysis of a low-temperature Mossbauer spectrum. The saturation magnetization and the anisotropy energy were found to be 234 emu/cc and 6.9 Merg/cm3, respectively. These values coincide with those of bulk-like single-phase α”-Fe16N2 particles. This crystalline anisotropy is still smaller than the shape anisotropy of the thin films (2πMs2=20 Merg/cm3), and a perpendicular magnetic state is not expected for the thin-film form.